Everyday undergraduate experiences and the impact on students’ mental health: scoping review - Lopes de Faria, Elisângela (2025)
Objective: to analyze the state of the art on everyday experiences at graduation and the impact on students’ mental health. Methods: This is a scoping review according to Joanna Briggs Institute developed based on the recommendations of the PRISMA-ScR international guide. Results: 26,862 records were retrieved and 38 studies were maintained for this review. Studies consider the prevalence of psychological distress in undergraduate students, causal factors, protective factors, gender predominance, professional counseling, suicide, among other issues. Conclusion: psychological distress in university students is associated with several factors; there is a low demand by students for help, little offer of reception services in universities, and the importance of institutions to strengthen and encourage programs to prevent risks and injuries and promote the mental health of university students.